(untitled) (Fiep Bulletin - online, 2014)
The curricular revisions are currently being in process in several countries in the European Union. The process of planning, projecting and designing national curriculum has always encountered various problems. In general the process has a political background and it may result from academic discussions or research based conclusions. Physical education has always played a very specific role in education. Although it has been a compulsory subject in primary and lower secondary education throughout the countries in Europe (Physical Education and Sport in Europe Eurydice Report, 2013), its position cannot be described as equivalent in comparison to the other subjects. One possible concept how to achieve a quality physical education is to standardize physical education in curricular documents, which could stress the importance of this subject. However, to accomplish this task is more difficult than someone would think. The learning outcomes are in European countries mostly defined qualitatively, but some of the countries report quantifiable outcomes (United Kingdom, Sweden, and Iceland). The paper tries to identify the principal problems of physical education curriculum development and presents a short introduction to planning and designing physical education aims, outcomes and standards in chosen European countries. We compare backgrounds of curriculum development specifically in Slovakia and the Czech Republic as the countries with common history but currently different approaches to projecting and designing national curriculum.